Performance Analysis of Locally Fabricated Electronic Electronic Rice Stink Bug (Leptocorisa Oratoriu. Fabricius) Control Device - Andres, J F (KnE Social Sciences, 2018)
The study analysed the performance of a locally fabricated electronic pester that basically intended to control the massive presence of rice stink bugs that destroys the performance of the development of rice grains by attracting and electrocuting the pest. The physical experimental method of the study was performed in the actual area of rice field at Narra, Palawan, Philippines. The experimental observation was conducted during the daytime from 8AM to 5AM which determines the effective height and distance of the device in controlling the rice stink bugs and the correlation of trapping the bugs using this locally fabricated electronic pester to the weather conditions. The result showed that there is no significant relationship between the established distance for capturing stink bugs at 2m, 3m, 4m and 5m distance separation, but it has a moderate correlation between the numbers of attracted stink bugs to the atmospheric temperature and negligible correlation to humidity. The height at ground level and 0.152 m. (0.5 ft) below the rice height attracted more stink bugs. At the different height of observation the attracted rice stink bugs has a moderate correlation to humidity, and it has no correlation to the atmospheric temperature. Thus, the result implies that the attracted stink bugs were not affected by the temperature at different height location of the device. The device was concluded as efficient which its 12VDC supply electronically step-up to electrocute the pest and recommended to consider having bigger size of attractant agent for possible more effective purpose. Keywords: Control device, rice stink bug, electronic